2013
DOI: 10.1111/camh.12022
|View full text |Cite
|
Sign up to set email alerts
|

Predicting length of stay and readmission for psychiatric inpatient youth admitted to adult mental health beds in Ontario, Canada

Abstract: Background The purpose of this study was to examine demographic, background, and psychopathology variables that predict length of stay and readmission among youth with mental health needs. Method We analyzed data on 2445 youth who were admitted into adult psychiatric beds in Ontario, Canada. Multiple regression was used to examine length of stay, whereas logistic regression was used to examine the predictors of readmission. Results Youth were likely to stay longer in hospital if they were older, were boys, had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…A further two studies identified ID as a potential risk factor among other demographic factors rather than assessing ID specifically (Stewart et al . ; Li et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…A further two studies identified ID as a potential risk factor among other demographic factors rather than assessing ID specifically (Stewart et al . ; Li et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found that 25% to 50% of children and youths do not receive aftercare (5,8,9). Furthermore, there is some evidence that those least likely to receive aftercare, including males, older children, those with lower socioeconomic status, and those living in rural areas, are most likely to be readmitted (7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…In addition, the aggregated data compiled as part of regular use can be employed for policy analysis, evaluation and research. Examples of peer-reviewed health services research based on interRAI MH data include: mental health needs of prisoners (264,265); mental health service planning (266); access to psychiatrists by linguistic minorities (267) and nursing home residents (268); use of ECT by psychiatric inpatients (269); prolonged stays (270,271); length of stay (272,273); and restrictions in movement in forensic patients (172). Examples of clinically oriented research with these data include studies of: sexual dysfunction (274,275); incontinence (276,277); discharges against medical advice (229,278); medication non-adherence and misuse (229,279,280); restraint and acute control medication use (281); and pharmacoepidemiological studies (282).…”
Section: Applications Of Interrai Instrumentsmentioning
confidence: 99%